2019
DOI: 10.1101/551671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graph Signal Processing of Low and High-Order Dynamic Functional Connectivity Networks Using EEG Resting-State for Schizophrenia: A Whole Brain Breakdown

Abstract: Schizophrenic subjects demonstrated a hypo-synchronization compared to healthy control group which can be interpreted as a low global synchronization of co-fluctuate functional patterns. Our analytic pathway could be helpful both for the design of reliable biomarkers and also for evaluating non-intervention treatments tailored to schizophrenia. EEG offers a low-cost environment for applied neuroscience and the transfer of research knowledge from neuroimaging labs to daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recent studies have utilized graph-based frameworks and GSP perspectives, enhancing our understanding of brain phenomena and interconnectivity among brain regions. These investigations have provided insights into brain signal classification [18,19], diagnosis of brain diseases [20][21][22][23], BCI [24][25][26], and graph frequency analysis of brain signals [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have utilized graph-based frameworks and GSP perspectives, enhancing our understanding of brain phenomena and interconnectivity among brain regions. These investigations have provided insights into brain signal classification [18,19], diagnosis of brain diseases [20][21][22][23], BCI [24][25][26], and graph frequency analysis of brain signals [27].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of artificial intelligence methods for the classification and detection of Schizophrenia (Lai et al, 2021), shows that MKL has been applied to both structural and functional Magnetic Resonance Images (MRI), increasing performance accuracy (Ulaş et al, 2012;Castro et al, 2014;Iwabuchi and Palaniyappan, 2017). Nevertheless, in this review MKL algorithms applied to electrophysiological data have been not reported, although a recent study used EEG dynamic functional connectivity networks to classify SZ based on MKL (Dimitriadis, 2019). To our knowledge, ERP data has not been used to classify SZ using MKL despite its use for other purposes such as brain-computer interfaces (Li et al, 2014;Yoon and Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography (EEG) on the other hand provides a reasonable alternative with -albeit lower spatial, but -much higher temporal resolution, thus allowing for a more detailed reconstruction of network dynamics. Despite this and other advantages of EEG imaging (i.e., its accessibility and mobility), up to date not many studies have used dynamic graph analysis of electrophysiological recordings to investigate DFC in SZ (Dimitriadis, 2019).…”
Section: Introductionmentioning
confidence: 99%